2016
DOI: 10.1016/j.ibmb.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta

Abstract: Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
178
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 269 publications
(324 reference statements)
3
178
1
Order By: Relevance
“…In the other, six sets of S. litura chromosomes were fused, corresponding to six H. melpomene chromosomes (N = 21) 11 , and another eight S. litura chromosomes were fused, corresponding to four other H. melpomene chromosomes. These changes were consistent with previous reports on chromosome evolution among butterflies including Melitaea cinxia 12 and the moth Manduca sexta 13 …”
Section: Articlessupporting
confidence: 93%
“…In the other, six sets of S. litura chromosomes were fused, corresponding to six H. melpomene chromosomes (N = 21) 11 , and another eight S. litura chromosomes were fused, corresponding to four other H. melpomene chromosomes. These changes were consistent with previous reports on chromosome evolution among butterflies including Melitaea cinxia 12 and the moth Manduca sexta 13 …”
Section: Articlessupporting
confidence: 93%
“…S3A), this report shows that an spz gene is involved in the melanization process. It has been reported that Spz-1 works as a ligand of Toll-1 and that the Toll signaling pathway is involved in dorsoventral axis formation (19), muscle development during embryogenesis (32), and the induction of antimicrobial peptide expression in innate immunity (33,34) (Fig. 5B).…”
Section: Discussionmentioning
confidence: 95%
“…5B). The initial step in both pathways is to recognize the lysine-containing peptidoglycan and β-1,3-glucan from the cell wall of Gram-positive bacteria and fungi by peptidoglycan recognition proteins and β-1,3-glucan recognition proteins, respectively, which are followed by independent serine-protease cascades in the two pathways (33,34) (Fig. 5B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations